Development of a Semantic Ontology for Knowledge of Ancient Lanna Documents - Julrode, Phichete; Jarusawat, Piyapat (ECTI Transactions on Computer and Information Technology (ECTI-CIT), 2025)
This study is a research and development project aimed at developing a semantic ontology for ancient Lanna documents. It focuses on building a structured relationship of knowledge by analyzing information from various documents and databases, including the research database, the online information resource database (OPAC), the Northern Thai Information Center of the Chiang Mai University Library, the online information resource database of Rajamangalaphisek National Library, Chiang Mai, the online information resource database (OPAC) of the National Library of Thailand, the Oce of Arts and Culture, Chiang Mai Rajabhat University, and the online database from Sirindhorn Anthropological Center. This research tackles inefficiencies in retrieving and managing information on ancient Lanna documents through the development of a semantic ontology. The aim is to enhance the organization, classification, and accessibility of these documents, thereby improving search capabilities and knowledge dissemination. The innovation of this research lies in the development and evaluation of a semantic ontology specifically tailored for ancient Lanna documents. This ontology facilitates more effective grouping, categorization, and retrieval of information, significantly enhancing access to and utilization of ancient knowledge. A key innovation of this research is the application of ontology and semantic web technologies to the study of ancient Lanna documents. The research presents a structured approach to developing and validating the ontology, utilizing tools like Protégé and involving expert evaluations to ensure accuracy and relevance. The research process is divided into three stages. Stage 1 involves determining the need for an ontology by analyzing online data and grouping related keywords and phrases through the study of various information resources, including digital collections of ancient Lanna documents. Stage 2 focuses on developing the ontology using the Protégé program, which involves designing classes, setting main classes, subclasses, hierarchies, and properties to create data relations within each class. Stage 3 encompasses the ontology assessment, which is divided into two parts: evaluating the appropriateness of the ontology structure by experts through a questionnaire on class correlation validity and assessing word grouping in ancient Lanna documents. The study’s findings indicate that the identication of denitions, scope, and development objectives is appropriate (mean score = 0.88), with high scores in class grouping and ordering (score = 0.90), naming relationships and properties (score = 0.90), and the overall preciseness and appropriateness of the ontology development for ancient Lanna documents (score = 0.89).